Microwave Assisted Synthesis of Phenol-Formaldehyde Resole. Issue 4 (2007) - Bajia, Subhash Chandra; Swarnkar, Pawan; Kumar, Sudesh; Bajia, Birbal
Abstract : An efficient synthesis of phenol-formaldehyde resin has been achieved by using conventional as well as microwave irradiation. Resin samples were tested for their physical and chemical properties. The structures of the resins have been supported by their spectral analysis.